Radiation dose permitted in dentistry patients. A review - Pinto Nicodemo, Omar (2023)
In dental practice, the use of imaging has increased over the years, generating an increase in the radiation dose for the dental patient. One factor under discussion is the amount of dose used in patients, men, women and children, at different stages of their life, due to the scientific evidence of the harmful effects of ionizing radiation. This review of the literature analyzed the characteristics of radiation and its effects in relation to the doses administered, and its equivalences in dental practice in panoramic periapical radiographs and cone beam tomographies. A search of the literature was carried out in the main information sources such as Medline (via PubMed), ELSEVIER, SCIELO,　and LILACS, using the search terms with a date limitation of the last 10 years. The selected articles　had to include information regarding the keywords used, including "Dental Offices, Radiation Dose, X-Rays, Ambulatory Care".